Beyond Populism: Sources of EU-Skepticism in the Visegrad Group (Decentering European studies: perspectives on Europe from its beyond, 2025)
Within the European Union (EU), the Visegrad Group (Czechia, Hungary, Poland, and Slovakia), known as the V4, has gained the reputation of being a troublemaker because of its opposition to further European integration. Scholars have studied sovereignism among the V4 countries―which is manifest in their EU-skepticism, anti-immigration stance, and political and social conservatism― predominantly on the premise that it stems from the influence populist parties and their leaders have exerted on domestic audiences. This chapter contends that recent sovereignist trends are better explained by the presence of grassroots-level discontent, as citizens’ reservations toward the EU within the Group have emerged regardless of the rise of populist parties in the region. Through descriptive and interpretative quantitative methodologies, this research uses EU cross-national public opinion survey data to examine the political, social, and cultural contexts in which public attitudes toward European integration are shaped in the V4. Findings show that, although people there want to limit the power of the EU—in alignment with mainstream populist parties—they do not wish for their respective countries to leave the Union, realizing that the EU provides economic benefits. The study shows that people’s rejection of immigration and multiculturalism does not depend on their support for right-wing populist parties, instead stemming from their perceived threat of terrorism and loss of national identity. Conclusions thus debunk the notion that it is the V4’s populist parties that create an East-West divide in European values. Although Eastern Europeans are more conservative about social and political matters than Western Europeans, these attitudes are unrelated to party politics.